The impact of minimum age of employment regulation on child labor and schooling - Eric V. Edmonds; Maheshwor Shrestha (IZA Journal of Labor Policy, 2012)
Promoting minimum age of employment regulation has been a centerpiece in child labor policy for the last 15 years. If enforced, minimum age regulation would change the age profile of paid child employment. Using micro-data from 59 mostly low-income countries, we observe that age can explain less than one percent of the variation in child participation in paid employment. In contrast, child-invariant household attributes account for 63 percent of the variation in participation in paid employment. While age may explain little of the variation in paid employment, minimum age of employment regulation could simultaneously impact time allocation. We do not observe evidence consistent with enforcement of minimum age regulation in any country examined, although light work regulation appears to have been enforced in one country.
Keywords: J22; O15; J88; K42; 330; Kinderarbeit; Altersgruppe; Arbeitsrecht; Entwicklungsländer; Entwicklungsländer